Essays on empirical banking - Amoni, Pedro Henrique Duca (2024)
This dissertation consists of three independent chapters empirically analyzing topics of banking. As a common element, they all study factors influencing the supply of credit and its consequences on the real economy. The first chapter studies how court decisions affect banks’ perception regarding creditors’ rights protection. Exploring the random distribution of cases among judges from the same district, I show that banks restrict credit immediately after observing unfavorable decisions in their legal disputes due to facing more lenient judges. This informational shock is transmitted to firms in banks’ relationships, leading to credit rationing for small companies and negatively impacting their performance. This work highlights the relevant role judges play in influencing economic activity beyond the parties involved in the process they judge. The second chapter studies the regional reallocation of credit after the Brazilian trade liberalization in the early 1990s. I show that areas more exposed to tariff reductions experienced capital outflows, banks reduced their exposure in hard-hit localities, and the reallocation of credit depends on financial connections between regions. Conditional on the direct effect of economic opening, areas that witnessed growth in the volume of credit due to reallocation experienced better job market outcomes for companies in the nontradable sector. Finally, the third chapter documents the real effects of an increase in the supply of credit by public banks outside of a period of crisis in Brazil. The intervention studied began in 2011, and to overcome potential endogeneities of the distribution of government-owned banks, I explore the acquisition of a state bank by a federal bank two years earlier to create treatment and control groups. The results indicate that municipalities that witnessed the entry of the federal bank due to the previous acquisition experienced a large increase in credit supply. However, these same municipalities observed a reduction in local product and wages in the nontradable sector. These findings align with the idea of credit misallocation harming aggregate economic performance.